The role of gratitude and optimism on the resilience of covid-19 survivors - Lestari, Rini; Prasetyaningrum, Juliani; Imadanty, Aqilah Larasati (University of Muhammadiyah Malang, 2024)
COVID-19 survivors need to maintain their mental health to return to their regular life after recovering from COVID-19. One of the psychological resources that promote mental health is resilience. Resilience has been studied, but it is still rarely studied in COVID-19 survivors. Resilience can be affected by gratitude and optimism. This study examines the role of gratitude and optimism in the resilience of COVID-19 survivors. This study is a quantitative, correlational study. The population was students of COVID-19 survivors at the University of Muhammadiyah Surakarta. The sampling technique used was purposive sampling. The sample included 114 students who survived COVID-19, consisting of 36 men and 78 women aged 18–23. Data were collected using a gratitude scale, an optimism scale, and a resilience scale. Data analysis was conducted by multiple regression. The results show that gratitude and optimism have a role in the resilience of COVID-19 survivors. Gratitude has a positive effect on resilience, and optimism also positively affects resilience. Gratitude and optimism have a 35.9% role in the resilience of COVID-19 survivors. However, gratitude has a higher position than optimism in enhancing the resilience of COVID-19 survivors. The implication of this research is to increase resilience in COVID-19 survivors by increasing gratitude and optimism.